2013
DOI: 10.1007/s00606-013-0891-x
|View full text |Cite
|
Sign up to set email alerts
|

Pros and cons of using genomic SSRs and EST-SSRs for resolving phylogeny of the genus Gossypium

Abstract: The genus Gossypium is comprised of 50 diverse cotton species representing eight different genomes (A through G and K), however, phylogenetic relationship using various DNA marker types such as RAPD and SSRs was determined on limited number of cotton species. In this report, we have demonstrated the application of genomic SSRs (gSSRs) and EST-SSRs, and after combining both the data sets, for resolving the phylogenies of 36 cotton species including seven races. Out of the 100 primer pairs surveyed (50 for gSSRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 73 publications
2
23
0
1
Order By: Relevance
“…eSSRs are preferred as anchor markers in comparative mapping studies due to their high transferability rate among related species unlike microsatellites from non-transcribed DNAs (Cavagnaro et al 2010). However, due to high selection pressure, eSSRs are less polymorphic compared to gSSRs (Tabbasam et al 2014).…”
Section: Communicated By D Grattapagliamentioning
confidence: 99%
“…eSSRs are preferred as anchor markers in comparative mapping studies due to their high transferability rate among related species unlike microsatellites from non-transcribed DNAs (Cavagnaro et al 2010). However, due to high selection pressure, eSSRs are less polymorphic compared to gSSRs (Tabbasam et al 2014).…”
Section: Communicated By D Grattapagliamentioning
confidence: 99%
“…The EST-SSR markers are developed using coding sequences that are more conserved than noncoding sequences. Since the genomic SSR markers are often derived from noncoding genomic sequences, higher levels of polymorphism are expected in genomic SSR markers than EST-SSR markers (Guo et al, 2007;Hu et al, 2011;Mujaju et al, 2013;Tabbasam et al, 2013). However, both EST-SSR and genomic SSR markers used in this study showed comparable ranges for the PIC values.…”
Section: Resultsmentioning
confidence: 73%
“…The three sets of SSR markers generated different dendrograms. This discrepancy was previously reported in other crop species and could be due to different genomic regions covered by both the markers and the variation in number of markers (Tabbasam et al, 2013;Parthiban et al, 2018). In addition, the EST-SSR markers are derived from expressed sequences compared to genomic sequences that are spread throughout the genome.…”
Section: Genetic Diversity Analysis and Cultivar Identificationmentioning
confidence: 72%
“…It is worth mentioning that all these markers have been derived from EST-SSRs and SSRs of G. hirsutum, and are successfully amplified in both the cotton species. Transferability between different species has also been demonstrated in several crop species (Kuleung et al, 2004;Saha et al, 2004) and also in the genus Gossypium (Tabbasam et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…In cotton, availability of DNA markers (functional or structural) with high allelic variability which are transferable to other cotton species is important for undertaking genetic analysis. For example such markers can help in conducting QTL mapping, comparative mapping, gene-flow and allelic profile studies in cotton (Tabbasam et al, 2014). In this study, each of the alleles amplified by JESPR-156 and MGHES-15 in G. arboreum was introgressed in one of the BC4F2 plants showing the low introgression rate of donor genome in succeeding backcross populations.…”
Section: Microsatellite Analysis For Introgressionmentioning
confidence: 73%